Postapproval Comparative Safety Study of Tofacitinib and Biological Disease‐Modifying Antirheumatic Drugs: 5‐Year Results from a United States–Based Rheumatoid Arthritis Registry - Kremer, Joel M.; Bingham, Clifton O.; Cappelli, Laura C.; Greenberg, Jeffrey D.; Madsen, Ann M.; Geier, Jamie; Rivas, Jose L.; Onofrei, Alina M.; Barr, Christine J.; Pappas, Dimitrios A.; Litman, Heather J.; Dandreo, Kimberly J.; et al. (ACR open rheumatology, 2021)
Objective Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). We compared 5‐year adverse event (AE) incidence rates (IRs) between patients initiating tofacitinib and those initiating new biological disease‐modifying antirheumatic drugs (bDMARDs) within the United States (US) Corrona RA registry. Methods IRs (number of first events/100 patient‐years) of major adverse cardiovascular events (MACE), serious infection events (SIEs), herpes zoster (HZ), malignancies, and death were estimated among tofacitinib and bDMARD initiators, regardless of dose/schedule, between November 6, 2012 (US Food and Drug Administration tofacitinib approval), and July 31, 2018 (follow‐up through January 31, 2019). Propensity score (PS) methods were used to control for nonrandom prescribing practices. Hazard ratios (HRs) were calculated to compare rates using multivariable‐adjusted Cox regression. Different risk windows were used for acute (MACE, SIEs, HZ, and venous thromboembolic events [VTEs]) and long‐term (malignancy and death) events. VTEs were assessed descriptively. Results For MACE, SIEs, and HZ, 1999 (3152.1 patient‐years) and 8358 (12 869.4 years) tofacitinib and bDMARD initiators were included, respectively; for malignancy/death, 1999 (4505.6 patient‐years) and 6354 (16 670.8 patient‐years) initiators were included, respectively. AE rates were similar across cohorts, except for HZ, which was significantly higher with tofacitinib versus bDMARDs (PS‐trimmed adjusted HR 2.32; 95% confidence interval [CI] 1.43‐3.75). There were 45 (zero serious) and 88 (five serious) HZ events with tofacitinib and bDMARDs, respectively. Sensitivity analyses demonstrated similar results. VTE IRs (95% CI) were 0.29 (0.13‐0.54) and 0.33 (0.24‐0.45) for tofacitinib and bDMARDs, respectively. Conclusion In this registry analysis, both cohorts had similar MACE, SIE, malignancy, death, and VTE rates; HZ rates were higher for tofacitinib initaitors than for bDMARD initiators.